Phonological regularity, perceptual biases, and the role of phonotactics in speech error analysis. Issue 5 (30th May 2018) - Alderete, John; Tupper, Paul
Abstract : Speech errors involving manipulations of sounds tend to be phonologically regular in the sense that they obey the phonotactic rules of well‐formed words. We review the empirical evidence for phonological regularity in prior research, including both categorical assessments of words and regularity at the granular level involving specific segments and contexts. Since the reporting of regularity is affected by human perceptual biases, we also document this regularity in a new data set of 2, 228 sublexical errors that was collected using methods that are demonstrably less prone to bias. These facts validate the claim that sound errors are overwhelmingly regular, but the new evidence suggests speech errors admit more phonologically ill‐formed words than previously thought. Detailed facts of the phonological structure of errors, including this revised standard, are then related to model assumptions in contemporary theories of phonological encoding. This article is categorized under: Linguistics > Linguistic Theory Linguistics > Computational Models of Language Psychology > Language Abstract : Speech errors tend to respect rules of possible sound combinations (= phonotactics), though less so than suggested by prior research due to perceptual biases. The patterns of regular sound combinations arise from syllable structure, output biases favoring frequent sounds and sequences, implicit learning, feature specification, and baseline frequencies.